2019
DOI: 10.1016/j.ejvs.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Neck Injury in Two Dutch Level 1 Trauma Centres: the Non-Existent Problem

Abstract: WHAT THIS PAPER ADDS This evidence driven clinical scenario summarises guideline recommendations regarding management of penetrating neck injuries (PNIs) and associated carotid artery injury, for (European) surgeons confronted with this potentially complex problem. When comparing these recommendations to PNI management in two Dutch level 1 trauma centres, it appears that CTA scanning has taken a more prominent role in PNI management than that described in guidelines. Furthermore, to explain clinical decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
1
23
0
4
Order By: Relevance
“…Zone II, being the most exposed part of the neck, is the most affected by injuries in our series, as it is reported similarly by most authors worldwide. [ 2 11 13 14 16 17 18 19 20 21 22 23 26 ] The midline of the neck is the most affected side among our patients. A similar finding was reported by de Régloix et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zone II, being the most exposed part of the neck, is the most affected by injuries in our series, as it is reported similarly by most authors worldwide. [ 2 11 13 14 16 17 18 19 20 21 22 23 26 ] The midline of the neck is the most affected side among our patients. A similar finding was reported by de Régloix et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 11 13 14 16 17 18 19 20 21 22 23 24 ] However, in slight contrast, Seok and Cho[ 25 ] reported a higher median age of 54.3 years, while Hundersmarck et al . [ 26 ] reported a median age of 40 years. These injuries are common in this age group and gender because they constitute the most active part of most societies and are more likely to be exposed to violence and accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when patients arrive at the hospital, depending on their symptoms and vitality, they may be examined, undergo an operation immediately, or undergo conservative treatments. The clinical significance of the no zone approach, which is based on symptoms, has been reported recently [16,17]. According to Nowicki et al [18], the no zone approach to penetrating neck injury evaluation and management is contemporary and goes against the grain of anatomical zones management.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of operation and CT scan trials differed for each study. Hundersmarck et al [17] reported that operation was performed in 54% of total patients, CT scan was 72.1%, and positive FNFs was 53.5%. Ibraheem et al [11] described different results wherein the operation rate was 36.2%, CT scan rate was 66.1%, and positive FNFs rate was 59.8%.…”
Section: Discussionmentioning
confidence: 99%